Evaluation of Global Islamophobia Trends: A Literature Review of Social Impacts and Countermeasures - Moh Saleh; Fathurrahman Muhtar; Suhirman; Abdul Fattah; Ismail Tholib (International journal of technology and education research, 2026)
The phenomenon of Islamophobia has increased significantly in recent decades and has evolved from individual prejudice to a systemic global problem. This study aims to analyze global Islamophobia trends by examining the causal factors, social impacts, and the effectiveness of countermeasures. The method used is a qualitative approach through library research using content analysis and thematic analysis techniques on various reputable academic sources over the past ten years. The results indicate that the rise in Islamophobia is influenced by three main factors: the politicization of identity for the sake of power, biased media construction, and minimal social interaction exacerbated by disinformation in the digital space. The resulting impacts are multidimensional, including economic discrimination, mental health disorders, identity crises, and weakened social cohesion in multicultural societies. Meanwhile, countermeasures efforts, both through international policies and social programs, still face various challenges, particularly in implementation and reach. This study emphasizes that addressing Islamophobia requires a comprehensive and integrated approach, encompassing strengthening legal regulations, improving digital literacy, and developing sustainable cross-cultural dialogue. In this way, it is hoped that a more inclusive, just and tolerant global social order will be created.